CD8+ T cells in situ in different clinical forms of human cutaneous leishmaniasis - Marina Loyola Dantas; Juliana Cabral de Oliveira; Lucas Carvalho; Sara Timoteo Passos; Adriano Queiroz; Paulo Machado; Edgar Carvalho; Sergio Arruda (Revista da Sociedade Brasileira de Medicina Tropical, 2013)
Introduction Leishmania braziliensis infection induces a large spectrum of lesions that clinically manifest as nodules or papules that progress to ulcers. Although it is already known that T helper cells predominate in the lesions, cytotoxic T cells have also been reported to be present, and their role in leishmaniasis immunopathogenesis is not well known. This study investigated the amounts of CD8+ and granzyme B+ cells in different clinical forms of human cutaneous leishmaniasis (CL). Methods Forty tissue fragments from early (E-CL) and late CL (L-CL) lesions and from disseminated leishmaniasis (DL) - papules and ulcers - were characterized. The inflamed area per fragment was calculated, and the CD8 and granzyme B expression levels in the infiltrates were quantified by counting positive cells in 15 fields. The localization of CD8 and granzyme B was graded subjectively. Results Inflammation was higher in L-CL and DL ulcers. CD8 expression was increased in late ulcerated lesions compared to recent lesions. The increase in CD8+ cells also correlated with the duration of the lesion. Papules had a higher frequency of granzyme B+ cells than E-CL lesions, although the frequency was similar to those for late and DL ulcers. CD8+ cells were mostly found in the papillary dermis. Conclusions CD8+ T and granzyme B+ cells are present in the inflammatory infiltrates of CL and DL and may participate in the immunopathogenesis of Leishmania infection.